HUBUNGAN ANTARA KELEKATAN ORANGTUA DENGAN REGULASI EMOSI REMAJA PONDOK PESANTREN AGRO “NUUR EL-FALAH” SALATIGA - Rahma Ajeng Pawulan; Lobby Loekmono; Sapto Irawan (PSIKOLOGI KONSELING, 2018)
This study aims to determine the sicnificance of the relationship between parent attachment and emotional regulation of adolescents Agro "Nuur El-Falah" Islamic Boarding School, Salatiga, Central Java. The subjects of this study were 123 students of the Salatiga Agro "Nuur El-Falah" Islamic Boarding School who were at the high school / vocational high school level. Data collection tools used are the Emotion Regulation Questionnaire by Gross and John (2003) and the Inventory of Parent and Peer Attachment by Armsden and Greenberg (2009). The analysis used is Pearson Product Moment Correlation analysis using SPSS version 20.0. The results of data analysis show that there is a significant positive relationship between parent  attachment and emotional regulation. Correlation value (r) between mother attachment with emotion regulation is 0,453 (P = 0,000 <0,05) and correlation coefficient value (r) father attachment with emotion regulation is 0,492 (P = 0,000 <0,05). Keywords : Parent Attachment, Emotion Regulation, Adolescents